A Novel Homozygous Mutation in the EC1/EC2 Interaction Domain of the Gap Junction Complex Connexon 26 Leads to Profound Hearing Impairment. (16th January 2014) - Birkenhäger, Ralf; Prera, Nicola; Aschendorff, Antje; Laszig, Roland; Arndt, Susan
Abstract : To date, about 165 genetic loci or genes have been identified which are associated with nonsyndromal hearing impairment. In about half the cases, genetic defects in the GJB2 gene (connexin 26) are the most common cause of inner-ear deafness. The genes GJB2 and GJB6 are localized on chromosome 13q11-12 in tandem orientation. Connexins belong to the group of "gap junction" proteins, which form connexons, each consisting of six connexin molecules. These are responsible for the exchange of ions and smaller molecules between neighboring cells. Mutational analysis in genes GJB2 and GJB6 was brought by direct sequencing of the coding exons including the intron transitions. Here we show in the participating extended family a homozygous mutation c.506G>A, (TGC>TAC) p.Cys169Tyr, in the GJB2 gene, which could be proven for the first time and led to nonsyndromal severe hearing impairment in the afflicted patients. The mutation is located in the EC1/EC2 interaction complex of the gap junction connexon 26 complex and interrupts the K + circulation and therefore the ion homeostasis in the inner ear. The homozygous mutation p.Cys169Tyr identified here provides a novel insight into the structure-function relationship of the gap junction complex connexin/connexon 26.